Using biofilter packed with different wood waste charges for purification of air contaminated with benzene - Vaiškūnaitė, Rasa (International Conference “Environmental Engineering”, 2020)
The main aim of this work was the analysis and assessment of benzene removal from air using bio-filter packed with a mixture of wood waste. The results of this work show that the small scale bio-filter with various coniferous and deciduous wood waste charges is capable of efficiently removing benzene from polluted air stream. The analysis of different mixtures of wood waste charge, while pH value was kept at neutral (pH = 7), determined, that the best wood waste mixture is consisted of 70% coniferous wood (45% pine trees, 25% fir trees), 30% deciduous wood (20% maple, 10% hazel) which was consisted of 10–20 mm fraction particles and had porosity value of 46%. This bio-media was best used for benzene removal from contaminated air stream (E = 93.86–74.78%).